2014
DOI: 10.2169/internalmedicine.53.1415
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction Caused by Coronary Embolism from <i>Aspergillus</i> Endocarditis

Abstract: Although the primary cause of acute coronary syndrome is atherosclerotic disease, it is important to include other causes of acute myocardial infarction. This report describes the case of a 53-year-old man with acute myeloid leukemia, who was referred to our cardiology department for treatment of acute myocardial infarction with ST segment elevation on an electrocardiogram. Portable echocardiography showed large areas of vegetation on the anterior mitral leaflet, while coronary angiography demonstrated the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…On day 21 of the treatment, the patient was diagnosed with acute pancreatitis, resulting in a discontinuation of L-asparaginase. During the im- Combined IFD treatment has a sound theoretical rationale, demonstrated in in vitro studies, animal models, and limited clinical data, including a randomized clinical trial involving a com- Similarly, there is limited experience with reference to the treatment of fungal endocarditis caused by Aspergillus species in hematologic patients [16][17][18][19][20]. Many factors might have impacted the failure of antifungal treatment of massive and disseminated aspergillosis in a pediatric patient with acute lymphoblastic leukemia.…”
Section: Case Descriptionmentioning
confidence: 99%
“…On day 21 of the treatment, the patient was diagnosed with acute pancreatitis, resulting in a discontinuation of L-asparaginase. During the im- Combined IFD treatment has a sound theoretical rationale, demonstrated in in vitro studies, animal models, and limited clinical data, including a randomized clinical trial involving a com- Similarly, there is limited experience with reference to the treatment of fungal endocarditis caused by Aspergillus species in hematologic patients [16][17][18][19][20]. Many factors might have impacted the failure of antifungal treatment of massive and disseminated aspergillosis in a pediatric patient with acute lymphoblastic leukemia.…”
Section: Case Descriptionmentioning
confidence: 99%
“…A recent study by Tillquist et al examining unplanned reintubation occurring in phase I or phase II recovery in the postanesthesia care unit identified risk factors such as extremes of age, higher American Society of Anesthesiologists physical status, and thoracic or vascular surgery. 3 A 2011 study by Ramachandran et al, examining reintubation in the first 72 hours after surgery, reported a broader array of risk factors including very low and very high body mass index, concomitant pulmonary, cardiac, or hepatic disease, and high-risk surgeries. 4 Finally, Hua et al, in 2012 reported an analysis of risk factors for reintubation in the first 30 days postoperatively.…”
Section: To the Editormentioning
confidence: 99%
“…4 Echocardiographic findings have been reported in several articles. 3,6 In these articles, vegetations seen were attached to the myocardial wall, which explains the high false-negative results with TEE. In 1997, Lim et al showed images of Aspergillus vegetation attached to the papillary muscle using 2D TEE 7 ; however, the interpretation of the images were limited due to low resolution.…”
mentioning
confidence: 99%
See 2 more Smart Citations